Composite material catalyst MFe2O4 / NH2-MIL-68 (In)-x as well as preparation method and application thereof
MFe2O4/NH2-MIL-68(In)-x composite catalyst was prepared by loading spinel-type ferrite MFe2O4 on NH2-MIL-68(In)-x for COS in pyroxylamine synthesis exhaust gas The hydrolysis removal of the system has achieved efficient and low-cost COS removal, and solved the problems of low efficiency and catalyst poisoning in the prior art.
Patent Information
- Application Number
- CN202411626875.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-21
AI Technical Summary
The prior art has low efficiency and high cost in deep purification of carbonylsulfur (COS) in phenylamin synthesis waste gas, and catalysts are prone to poisoning, affecting industrial production.
The MFe2O4/NH2-MIL-68(In)-x composite catalyst is used, which forms a composite material by loading spinel-type ferrite MFe2O4 onto NH2-MIL-68(In) to form a composite material for catalyzing hydrolysis of benzene COS in thiacaminol synthesis exhaust gas.
At 120°C to 150°C, the COS removal rate reaches 92% to 96%, solving the problems of low hydrolysis conversion, high temperature, and catalyst poisoning. The preparation conditions are mild, the equipment is simple, and the energy consumption is low, and it is suitable for industrial applications.
Smart Images

Figure CN119488954A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of industrial catalysis, and specifically relates to a hydrolysis catalyst MFe2O4 / NH2-MIL-68(In)-x for removing carbonyl sulfide (COS) in mefenacet synthesis waste gas and a preparation method thereof. Background Art
[0002] Mefenacet, as an amide herbicide, exhibits significant cell growth and division inhibition activity. It is specially designed for transplanted rice fields and can effectively control the growth of grass weeds. It has excellent control effects on various types of barnyard grass, perennial cow hair felt and duckweed, and is particularly effective in controlling barnyard grass with large leaf ages.
[0003] At present, mefenacet is mainly produced by the phosgenation process. In the phosgenation reaction step, the malodorous gas carbonyl sulfide (COS) is produced. COS discharged into the atmosphere without treatment can form SO2 and eventually convert into sulfate aerosol, causing serious environmental pollution problems. Moreover, COS produced during the production process will not only corrode equipment and pipelines, but also easily cause catalyst poisoning in the downstream process flow, making it inactive, thereby affecting subsequent industrial production and product quality. Therefore, the removal of carbonyl sulfide is of great significance.
[0004] The main removal technologies of COS include reduction, hydrolysis, absorption, adsorption, photolysis and oxidation. Among them, the application of reduction, absorption, adsorption and photolysis methods is generally accompanied by a high cost burden, and is more suitable for fine COS removal operations in small-scale tail gas emissions. It seems powerless when facing the deep purification needs of COS in the synthetic waste gas of mefenacet. Compared with the hydrogenation reduction method, the catalytic hydrolysis method (the specific reaction formula is COS+H2O→H2S+CO) has won wide recognition in the field of COS conversion and removal due to its mild reaction environment, low operating temperature range, good removal efficiency and fewer side reactions. The key factor that determines the efficiency and effect of the hydrolysis method is the choice of catalyst.
[0005] Carbonyl sulfide hydrolysis catalysts often use porous materials with large specific surface areas. These materials have gradually evolved from traditional activated carbon, metal oxides (γ-Al2O3, TiO2, etc.), molecular sieves and clays to metal organic framework materials (MOFs) that have attracted much attention in recent years. MOFs can not only provide abundant adsorption sites, but also effectively capture COS molecules. They can also achieve optimized interactions with COS molecules by precisely designing the pore size and shape in their structure, thereby significantly improving adsorption efficiency and selectivity. Chinese patent CN 106622381A discloses a Fe-MOF catalyst, which successfully synthesizes FeBTC catalysts by controlling the volume fraction of ethanol solution to 66.7% to 80%. The obtained FeBTC catalyst can be used in the catalytic hydrolysis reaction of COS. Due to the large specific surface area of the prepared catalyst, the COS conversion rate is high, and the conversion activity can reach 78.11%. However, the Fe-MOF catalyst is synthesized by electrochemical method. Although the electrochemical method is more conducive to the formation of crystal form and the purity of the product is often higher, the electrochemical method itself has high energy consumption and complex equipment, so it is not suitable for large-scale industrial production. In addition, with the deepening of research, the thermal stability and chemical stability of MOFs also need to be continuously improved, mainly to enable such materials to adapt to more stringent operating conditions and further demonstrate their great potential in the field of COS removal.
[0006] Through research, it is found that MIL-68(In)-NH2 is a MOFs material with good hydrothermal stability and high specific surface area, and the free amino group it carries faces the center of the pore structure. Due to the confinement effect of the pore, large-sized substrates cannot enter the pore, while small-sized substrates can enter the pore and react with the amino active sites to be adsorbed. Therefore, if the MIL-68(In)-NH2 metal organic framework material with good selective adsorption performance can be used in catalytic reactions, it may promote the catalytic reaction. However, in the prior art, this material is mainly used to treat high-concentration dye wastewater in water bodies. The MOFs material has not yet been successfully applied in the field of catalytic reactions, and the specific application scheme and application effect need to be further explored. Summary of the invention
[0007] In order to solve the deficiencies in the prior art, the present invention provides a composite catalyst MFe2O4 / NH2-MIL-68(In)-x and a preparation method thereof, and an application thereof in catalyzing the hydrolysis of carbonyl sulfide in the waste gas of mefenacet synthesis.
[0008] In order to achieve the above technical objectives, the present invention is implemented through the following technical scheme: a composite material catalyst MFe2O4 / NH2-MIL-68(In)-x, which is a composite material formed by loading spinel ferrite MFe2O4 onto NH2-MIL-68(In) using NH2-MIL-68(In) as a carrier, wherein M represents Co or Cu, x represents the percentage of MFe2O4 in the composite material, and x ranges from 10 to 60, in units of %.
[0009] The preparation method of the composite catalyst MFe2O4 / NH2-MIL-68(In)-x is as follows:
[0010] 1) Add NH2-MIL-68(In), Co(II) salt or Cu(II) salt, and Fe(III) salt into deionized water respectively, mix well, and obtain solution A;
[0011] 2) dissolving an inorganic base in deionized water to obtain solution B;
[0012] 3) Under continuous stirring, solution B is added dropwise to solution A to form a mixed solution, the mixed solution is heated in an oil bath and then subjected to a hydrothermal reaction, cooled to room temperature, washed, and dried to obtain a MFe2O4 / NH2-MIL-68(In)-x composite catalyst.
[0013] Furthermore, in step 1), the Co(II) salt is selected from one or more of CoCl2 or its hydrate, Co(NO3)2 or its hydrate, CoSO4 or its hydrate; the Cu(II) salt is selected from one or more of CuCl2 or its hydrate, Cu(NO3)2 or its hydrate, CuSO4 or its hydrate.
[0014] Furthermore, in step 1), when Co(II) salt is used to prepare solution A, the mass ratio of Co element in Co(II) salt to NH2-MIL-68(In) is 1:5~18, and when Cu(II) salt is used to prepare solution A, the mass ratio of Cu element in Cu(II) salt to NH2-MIL-68(In) is 1:3~18; the mass ratio of Fe element in Fe(III) salt to NH2-MIL-68(In) is 1:2~10.
[0015] Furthermore, in step 2), the inorganic base is any one or a combination of NaOH, KOH, LiOH, and CsOH, and the concentration of the inorganic base in solution B is 0.15 to 1.0 mol·L -1 .
[0016] Furthermore, in step 3), the volume ratio of solution B to solution A is 1:1-4.
[0017] Furthermore, in step 3), the oil bath heating temperature is 80-100° C. and the oil bath heating time is 50-80 min.
[0018] Furthermore, in step 3), the hydrothermal reaction temperature is 180-280° C., and the hydrothermal reaction time is 18-36 h.
[0019] Furthermore, in step 3), the drying temperature is 60 to 80° C. and the drying time is 12 to 24 hours.
[0020] The above-mentioned composite catalyst MFe2O4 / NH2-MIL-68(In)-x can be used in the catalytic hydrolysis of carbonyl sulfide, and has a good COS removal effect. The COS removal rate can reach 92% to 96% at 120°C to 150°C, which solves the technical problems existing in the prior art such as low carbonyl sulfide hydrolysis conversion rate, high hydrolysis temperature, and easy poisoning of the hydrolysis catalyst.
[0021] The beneficial effects of the present invention are:
[0022] 1. This application uses the indium-based MOF material NH2-MIL-68 (In) with large specific surface area, adjustable pore size and good stability as a catalyst carrier, loads the spinel ferrite MFe2O4 onto the NH2-MIL-68 (In) carrier, designs and synthesizes MFe2O4 / NH2-MIL-68 (In)-x composite catalysts with suitable framework structure, pore structure and open metal active sites, and exerts their synergistic effects in gas adsorption and catalytic hydrolysis, and exhibits high catalytic activity and high selectivity in the COS hydrolysis catalytic process;
[0023] 2. The composite catalyst MFe2O4 / NH2-MIL-68(In)-x prepared by the method disclosed in the present application can be efficiently used for the removal of COS in the waste gas of the synthesis of mefenacet, solving the technical problems of low hydrolysis conversion rate, high hydrolysis temperature, and easy poisoning of the hydrolysis catalyst of the existing hydrolysis catalytic materials. In addition, the preparation conditions are mild, the required equipment is simple, the energy consumption is low, and it is suitable for industrial production and application;
[0024] 3. This application develops a new composite catalyst for COS hydrolysis, which further broadens the application of MOF in the field of gas phase catalysis, and is not limited to basic research fields such as gas adsorption and separation, hydrogen storage and liquid phase catalysis;
[0025] 4. The hydrolysis catalyst MFe2O4 / NH2-MIL-68(In)-x disclosed in the present application has certain magnetism, and can be quickly separated and recovered by an external magnetic field, and can be better recycled. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 is the X-ray diffraction pattern of CoFe2O4 / NH2-MIL-68(In)-20 prepared in Example 1;
[0027] Figure 2 is the infrared spectrum of CoFe2O4 / NH2-MIL-68(In)-20 prepared in Example 1;
[0028] Figure 3 The removal rate statistics of COS removal by using the composite materials prepared in Examples 1-4 as hydrolysis catalysts;
[0029] Figure 4 These are photographs of a magnetic recovery experiment on the CoFe2O4 / NH2-MIL-68(In)-20 composite material prepared in Example 1, wherein (a) is a photograph of the composite material in its natural state, and (b) is a photograph of the composite material recovered using a magnet. DETAILED DESCRIPTION
[0030] The following examples further illustrate the content of the present invention, but should not be construed as limiting the present invention. Without departing from the essence of the present invention, modifications and substitutions made to the methods, steps or conditions of the present invention all fall within the scope of the present invention.
[0031] The NH2-MIL-68(In) carrier used in the example is prepared according to the prior art, and the specific preparation method is not described in detail here.
[0032] Example 1
[0033] This embodiment discloses a method for preparing the composite material CoFe2O4 / NH2-MIL-68(In)-20, and the specific process is as follows:
[0034] 1) Add NH2-MIL-68(In) (0.9385 g), Co(NO3)2·6H2O (0.2910 g) and FeCl3·6H2O (0.2703 g) into 50 mL of deionized water, ultrasonicate and stir for 60 min at room temperature to obtain solution A;
[0035] 2) Dissolve NaOH (0.4000 g) in 40 mL of deionized water to obtain solution B.
[0036] 3) Add solution B dropwise into solution A under continuous stirring, transfer the mixed solution to an oil bath, and heat and stir at 90°C for 60 min;
[0037] 4) The mixed solution was transferred to a hydrothermal reactor, heated at 200°C for 24 hours, cooled to room temperature, washed with deionized water three times, and the obtained solid powder was dried in a vacuum drying oven at 60°C for 12 hours to obtain a CoFe2O4 / NH2-MIL-68-20 composite material.
[0038] Figure 1 This is the X-ray diffraction pattern of the composite material prepared in this embodiment. It can be seen from the figure that the characteristic diffraction peaks of CoFe2O4 (220), (311), (400), (511), and (311) appear at 2θ angles of 30.1°, 35.4°, 43.1°, 56.9°, and 62.6°, and the characteristic diffraction peaks of NH2-MIL-68(In) are observed at 2θ angles of 8.08°, 9.36°, 16.16°, and 18.84°, proving that CoFe2O4 / NH2-MIL-68(In) is successfully composited.
[0039] Observe the infrared spectrum of the composite material prepared in this embodiment ( Figure 2 ), at 3460cm -1 and 3376cm -1 The absorption peak at 1555cm is attributed to the symmetric and asymmetric stretching vibration of N—H in NH2-MIL-68(In). -1 The absorption peak at 1383 cm is attributed to the stretching vibration of the C=O bond. -1 The absorption peak at 592 cm is attributed to the stretching vibration of CN; -1 and 405cm -1 The absorption peaks are attributed to the absorption of Co-O and Fe-O bonds in CoFe2O4.
[0040] The composite material prepared in this embodiment was subjected to a magnetic recovery experiment, and the effect was shown in Figure 4 As can be seen from the figure, the obtained composite material has magnetic properties. When used later, the material can be quickly separated and recovered through an external magnetic field, making it convenient for recycling.
[0041] Example 2
[0042] This embodiment discloses a method for preparing a composite material CuFe2O4 / NH2-MIL-68(In)-20, and the specific process is as follows:
[0043] 1) Add NH2-MIL-68(In) (0.9568 g), CuCl2·2H2O (0.1705 g) and FeCl3·6H2O (0.5406 g) to 50 mL of deionized water, ultrasonicate and stir for 60 min at room temperature to obtain solution A;
[0044] 2) Dissolve NaOH (0.4000 g) in 40 mL of deionized water to obtain solution B;
[0045] 3) Add solution B dropwise into solution A under continuous stirring, transfer the mixed solution to an oil bath, and heat and stir at 90°C for 60 min;
[0046] 4) The mixed solution was transferred to a hydrothermal reactor, heated at 200°C for 24 hours, cooled to room temperature, washed three times with deionized water, and the obtained solid powder was dried in a vacuum drying oven at 60°C for 12 hours to obtain a CuFe2O4 / NH2-MIL-68(In)-20 composite material.
[0047] Example 3
[0048] This embodiment discloses a method for preparing the composite material CoFe2O4 / NH2-MIL-68(In)-40, and the specific process is as follows:
[0049] 1) Add NH2-MIL-68(In) (0.3519 g), CoCl2·6H2O (0.2379 g) and FeCl3·6H2O (0.2703 g) to 80 mL of deionized water, ultrasonicate and stir for 60 min at room temperature to obtain solution A;
[0050] 2) Dissolve KOH (0.5610 g) in 20 mL of deionized water to obtain solution B.
[0051] 3) Add solution B dropwise into solution A under continuous stirring, transfer the mixed solution to an oil bath, and heat at 90°C with stirring for 60 min;
[0052] 4) The mixed solution was transferred to a hydrothermal reactor, heated at 200°C for 24 hours, cooled to room temperature, washed with deionized water three times, and the obtained solid powder was dried in a vacuum drying oven at 60°C for 12 hours to obtain a CoFe2O4 / NH2-MIL-68-40 composite material.
[0053] Example 4
[0054] This embodiment discloses a method for preparing the composite material CuFe2O4 / NH2-MIL-68(In)-40, and the specific process is as follows:
[0055] 1) Add NH2-MIL-68(In) (0.3588 g), Cu(NO3)2·2H2O (0.2416 g) and FeCl3·6H2O (0.5406 g) into 80 mL of deionized water, ultrasonicate and stir for 60 min at room temperature to obtain solution A;
[0056] 2) CsOH (1.500 g) was dissolved in 60 mL of deionized water to obtain solution B;
[0057] 3) Add solution B dropwise into solution A under continuous stirring, transfer the mixed solution to an oil bath, and heat and stir at 90°C for 60 min;
[0058] 4) The mixed solution was transferred to a hydrothermal reactor, heated at 200°C for 24 hours, cooled to room temperature, washed with deionized water three times, and the obtained solid powder was dried in a vacuum drying oven at 60°C for 12 hours to obtain a CuFe2O4 / NH2-MIL-68(In)-40 composite material.
[0059] Application Examples
[0060] The catalysts prepared in each embodiment were used in the activity test of COS catalytic hydrolysis. The test was carried out in a fixed bed quartz tube reactor with an inner diameter of 5 mm and a length of 200 mm. The test conditions were: catalyst loading m = 0.1 g, test temperature of 60°C to 160°C, COS concentration in the exhaust gas of 78 mg / m 3 , flow rate is 30mL / min, N2 is the balance gas. Each gas is gradually mixed through the mass flow meter, then water vapor is added through the water saturator, and finally enters the air mixer for full mixing. The COS concentration at the outlet of the fixed bed reactor is detected by gas chromatography.
[0061] The removal rate results are shown in Figure 3 The composite materials prepared in Examples 1-4 were used as hydrolysis catalysts to hydrolyze and remove COS from exhaust gas, and all showed good COS removal effects. A COS removal rate of 92-96% could be achieved at 120°C to 150°C. Such catalytic materials can be used in fixed bed reactors or moving bed reactors, and are suitable for the purification of gases containing carbonyl sulfide.
[0062] The above shows and describes the basic principles, main features and advantages of the present invention. However, the above is only a specific embodiment of the present invention, and the technical features of the present invention are not limited thereto. Any other implementation methods derived by any technician in the field without departing from the technical solution of the present invention should be included in the patent scope of the present invention.
Claims
1. A composite catalyst MFe2O4 / NH2-MIL-68(In)-x, characterized in that: It is a composite material formed by loading spinel ferrite MFe2O4 onto NH2-MIL-68(In) using NH2-MIL-68(In) as a carrier, wherein M represents Co or Cu, and x represents the percentage of MFe2O4 in the composite material, and x ranges from 10 to 60, in %.
2. The method for preparing the composite catalyst MFe2O4 / NH2-MIL-68(In)-x according to claim 1, characterized in that: The steps include: 1) Add NH2-MIL-68(In), Co(II) salt or Cu(II) salt, and Fe(III) salt into deionized water respectively, mix well, and obtain solution A; 2) dissolving an inorganic base in deionized water to obtain solution B; 3) Under continuous stirring, solution B is added dropwise to solution A to form a mixed solution, the mixed solution is heated in an oil bath and then subjected to a hydrothermal reaction, cooled to room temperature, washed, and dried to obtain a MFe2O4 / NH2-MIL-68(In)-x composite catalyst.
3. The method for preparing the composite catalyst MFe2O4 / NH2-MIL-68(In)-x according to claim 2, characterized in that: In step 1), the Co(II) salt is selected from one or more of CoCl2 or its hydrate, Co(NO3)2 or its hydrate, CoSO4 or its hydrate; the Cu(II) salt is selected from one or more of CuCl2 or its hydrate, Cu(NO3)2 or its hydrate, CuSO4 or its hydrate.
4. The method for preparing the composite catalyst MFe2O4 / NH2-MIL-68(In)-x according to claim 2, characterized in that: In step 1), when Co(II) salt is used to prepare solution A, the mass ratio of Co element in Co(II) salt to NH2-MIL-68(In) is 1:5-18, and when Cu(II) salt is used to prepare solution A, the mass ratio of Cu element in Cu(II) salt to NH2-MIL-68(In) is 1:3-18; the mass ratio of Fe element in Fe(III) salt to NH2-MIL-68(In) is 1:2-10.
5. The method for preparing the composite catalyst MFe2O4 / NH2-MIL-68(In)-x according to claim 2, characterized in that: In step 2), the inorganic base is any one or a combination of NaOH, KOH, LiOH, and CsOH, and the concentration of the inorganic base in solution B is 0.15 to 1.0 mol·L -1 .
6. The method for preparing the composite catalyst MFe2O4 / NH2-MIL-68(In)-x according to claim 2, characterized in that: In step 3), the volume ratio of solution B to solution A is 1:1-4.
7. The method for preparing the composite catalyst MFe2O4 / NH2-MIL-68(In)-x according to claim 2, characterized in that: In step 3), the oil bath heating temperature is 80-100° C. and the oil bath heating time is 50-80 min.
8. The method for preparing the composite catalyst MFe2O4 / NH2-MIL-68(In)-x according to claim 2, characterized in that: In step 3), the hydrothermal reaction temperature is 180-280° C. and the hydrothermal reaction time is 18-36 h.
9. The method for preparing the composite catalyst MFe2O4 / NH2-MIL-68(In)-x according to claim 2, characterized in that: In step 3), the drying temperature is 60 to 80° C. and the drying time is 12 to 24 hours.
10. Use of the composite catalyst MFe2O4 / NH2-MIL-68(In)-x as claimed in claim 1 in catalytic hydrolysis of carbonyl sulfide.
Citation Information
Patent Citations
Novel preparation method of Fe-MOF (ferrous-metal oxide framework) catalyst and application thereof in desulfurizing field
CN106622381A
Cited By
Microsphere core-shell structure catalyst, preparation method thereof and application of microsphere core-shell structure catalyst in carbonyl sulfide hydrolysis
CN121732171A